The implementation of 5s system in Yayasan Islam Terengganu: Impact on operating performances / Muhammad Izzuddin Mohd Zulkefli - Mohd Zulkefli, Muhammad Izzuddin (2011)
This paper is to explore and study the relationship between the 5S implementation and the impact on the operating performance of Yayasan Islam Terengganu. The performance measures refer to improvements in productivity, quality, employee satisfaction and lead time. The study would like to explore the effect on these variables with the implementation of 5S system. This study was conducted by using a questionnaire survey with 50 respondents the staff of Yayasan Islam Terengganu. The results show some inaccurate results but still the positive relationship between the implementation of 5S and the measurement taken can be seen. Moreover, 5S system is positively related to some operational performances measures, especially those referring to productivity and lead time